ESTUDIO PRELIMINAR DE LA ASOCIACIÓN ENTRE ESPECIES DE BOMBUS (HYMENOPTERA: APIDAE) Y LA FLORA DEL BOSQUE SERRANO EN CÓRDOBA (ARGENTINA) (Acta Entomológica Chilena, 2022)
This preliminary study reports the relationship between bumblebees and flowers of the Bosque Serranoin Córdoba, Argentina. There are three species of Bombus present in the area: moño, opifex and bellicosusObservations were made on the behavior of pollinators and flower syndromes. The results show that eachspecies of bumblebees presented a specific behavior when a particular plant was visited, but there are nodifferences between specimens.